Decentralization and International Tax Competition - John Wilson; Eckhard Janeba (Center for Economic Studies and ifo Institute (CESifo), 2003)
This paper models tax competition between two countries that are divided into regions. In the first stage of the game, the strategy variable for each country is the division of the provision of a continuum of public goods between the central and regional governments. In the second stage, the central and regional governments choose their tax rates on capital. A country's decentralization level serves as a strategic tool through its influence on the mix of horizontal and vertical externalities that exist under tax competition. In contrast to standard tax competition models, decentralizing the provision of public goods may be welfare-enhancing.
Keywords: 330